Procedures for Confiscation of Proceeds of Crime - Dahia, Abdellatif; Belouadah, Tayeb (Journal of Legal Studies and Researches, 2024)
This study aims to clarify how funds smuggled to another country were dealt with. We have clarified the procedural provisions for confiscating these funds, then measures for direct property recovery and confiscation without relying on a criminal conviction, and finally returning confiscated criminal proceeds to countries, as we concluded our study.